Physicochemical, Microbiological Characteristics of Meatballs from a Mixture of IPB D1 Chicken and Local Indonesian Rabbit Meats - Madjid, Syafira Amalia; Arief, Irma Isnafia; Wulandari, Zakiah; Sumantri, Cece (Malaysian Journal of Science, 2024)
IPB D1 chicken meat originates from a novel hybrid domestic chicken lineage, possessing nutritional attributes comparable to those found in rabbits. IPB D1 chicken and rabbit meat are rich in protein and minerals and can be used as the main ingredients for nutrient-rich food products, such as meatballs. This study aims to analyze the physicochemical, microbiological, and organoleptic characteristics of meatballs made with 100% chicken meat from IPB D1, 100% rabbit meat, and a combination of 50% chicken meat from IPB D1 and 50% rabbit meat. The meatballs were tested for their physical characteristics, such as pH, water activity, cooking loss, and texture profile, alongside chemical, microbiological, and sensory test characteristics to identify which formulation produced a meatball with optimal results. The study employed a completely randomized design. Results showed that meatballs with a composition of 50% IPB D1 chicken meat and 50% rabbit meat exhibited superior physical, chemical, microbiological, and sensory test outcomes. Results obtained from this study are promising for development into functional and diverse food products, as they have potential for commercial advancement.